ARE ISLAMIC BANKS SUFFERING FROM A MODEL MISFIT? A COMPARISON WITH COOPERATIVE BANKS - Rosana Gulzar; Mansor H. Ibrahim; Mohamed Ariff (Bank Indonesia, 2020)
For the first time, this study investigates whether Islamic banks, in mimicking conventional banks, have become less stable than their theoretical equivalent, which is the cooperative banks in Europe. Theoretically the interest prohibition should have pushed Islamic banks towards mutuality and profit-sharing, which have been argued to be stabilising. In practice however, the banks are pushed for growth under a debt-driven commercial banking model which is not only antithetical to the Shariah but also destabilising. This may explain why the empirical findings are still divergent in Islamic banking stability studies. Our study employs system GMM to compare the stability of 37 Islamic banks against 1,536 cooperative banks in Europe during the 2008 crisis and post-non-crisis years. Interestingly, we found consistent and significant evidence that the Islamic banks are less stable than the cooperative banks in both macroeconomic conditions. This has significant policy implications, main of which is to steer reform efforts away from refurbishing Islamic commercial banks and towards building an entirely new Islamic cooperative bank, based on the model in Europe.